Bianchi Type-I Cosmological Model with Perfect Fluid in Modified f(T) Gravity - Mete, V. G.; Dudhe, P. S.; Ingle, V. M. (Journal of Scientific Research, 2023)
In this paper, the Bianchi type I cosmological models with perfect fluid is investigated in the framework of f(T) theory of gravitation. The functional form of the function f(T) such as f(T) = T + βT2 is used for investigation. The physical and kinematical properties of the models are obtained and analyzed. We obtained an accelerating and expanding universe.